De novo transcriptome assembly of textile hemp from datasets on hypocotyls and adult plants - Behr, Marc (Data Brief, 2019)
We here provide an updated de novo transcriptome of the hemp textile variety Santhica 27. The assembly was performed by merging the reads obtained previously on a time-series relative to the hypocotyl development and on bast fibers isolated from internodes of adult plants at different heights with those obtained from a newly performed transcriptome study on the hypocotyl in response to jasmonic acid treatment. More specifically, hypocotyls aged 15 days were treated with jasmonic acid and collected 3 and 5 days after the application of the plant growth regulator. RNA-Seq was then performed on the treated hypocotyls. The transcriptome reported here will be a useful resource for those scientists engaged in the study of bast fiber development, as well as cell wall biosynthesis in textile hemp. The transcriptome is also useful for molecular studies relative to the synthesis of secondary metabolites, such as phenolic compounds (e.g. flavonoids) and lignans/lignanamides.